PENERAPAN PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Ade Evi Fatimah (Mahesa Research Center, 2020)
Realistic mathematics learning is learning that connects and engages the surrounding environment and real experiences that students have experienced in everyday life. The objectives of this study were (1) to find out how to apply realistic mathematics learning approaches to students' problem-solving abilities in fractions material. (2) To determine student learning activities on the application of realistic mathematics learning approaches to students' problem-solving abilities on fraction material. This study uses a descriptive analysis. The subjects in this study were 7th-grade students of SMP Tunas Pelita Binjai, while the objects in this study were the students' problem-solving abilities and student activities during learning. Based on the results of the analysis, it was obtained (1) The application of a realistic mathematics learning approach to students' problem-solving abilities on fractions in Grade 7 was to present contextual problems about fractions, solve contextual problems about fractions, then compare and discuss answers and conclude learning. Based on the learning process, a percentage of 80.55% of students obtained problem-solving abilities above the low category. This shows that the realistic mathematics approach is effective for building students 'problem-solving abilities. (2) Student learning activities on the application of realistic mathematics learning approaches to students' problem-solving abilities on fraction material in Grade 7 are in the good category with a final score of 80.14. So it can be suggested that in the teaching and learning process it is expected that the teacher uses a realistic mathematics learning approach.